Reflection and Transmission of Plane Wave at an Interface Between Two Rotating Micropolar Piezoelectric Solid Half-Spaces - SINGH, Baljeet; SANGWAN, Asha; SINGH, Jagdish (Archives of Acoustics, 2021)
In this paper, we investigate a problem on reflection and transmission of plane-waves at an interface between two dissimilar half-spaces of a transversely isotropic micropolar piezoelectric material. The entire model is assumed to rotate with a uniform angular velocity. The governing equations of rotating and transversely isotropic micropolar piezoelectric medium are specialized in a plane. Plane-wave solutions of two-dimensional coupled governing equations show the possible propagation of three coupled plane-waves. For an incident plane-wave at an interface between two dissimilar half-spaces, three reflected and three transmitted waves propagate with distinct speeds. The connections between the amplitude ratios of reflected and transmitted waves are obtained. The expressions for the energy ratios of reflected and transmitted waves are also obtained. A numerical example of the present model is considered to illustrate the effects of rotation on the speeds and energy ratios graphically.